Cultural Value and Psychological Empowerment on Innovative Work Behavior: The Moderating of Business Duration in Women MSME Entrepreneurs - Mery Atika; Vidya Nindhita; Fatimatuz Zahro; Mochamad Raka Erlangga; Ahmad Rosyad Hilmi (Universitas Ahmad Dahlan, 2026)
This study examines the influence of cultural values and psychological empowerment on innovative work behavior, with business duration as a moderating variable among women MSME entrepreneurs in Bangkalan Regency. A quantitative causal research design was employed, involving 272 respondents selected using an incidental sampling technique. Data were collected through self-report questionnaires using a five-point Likert scale, including measures of cultural values, psychological empowerment, and innovative work behavior. Data were analyzed using Moderated Regression Analysis (MRA) with IBM SPSS. The results indicate that both cultural values and psychological empowerment significantly predict innovative work behavior. Business duration was found to moderate the relationships between cultural values, psychological empowerment, and innovative work behavior. However, business duration did not show a significant direct effect on innovative work behavior, suggesting that experience alone is insufficient to drive innovation unless supported by cultural and psychological factors. The model explained 79.3% of the variance in innovative work behavior, indicating a strong combined contribution of the predictors. These findings highlight the importance of integrating cultural context and psychological empowerment in understanding innovation among women entrepreneurs. Practically, the results suggest that enhancing innovative work behavior requires not only business experience but also the strengthening of intrinsic motivation and the adaptive use of cultural values in business practices.